Equal Price for Equal Place? Demand-Driven Racial Discrimination in the Housing Market - Anthony Lepinteur; Giorgia Menta; Sofie R. Waltl (Institute of Labor Economics (IZA), 2023)
Participants to an online study in Luxembourg are presented with fictitious real-estate advertisements and tasked to make an offer for each of them. A random subset is also shown sellers' names that are strongly framed to signal their origins. Our randomised procedure allows us to conclude that, keeping everything else constant, a seller with a sub-Saharan African surname is systematically offered lower prices. Our most conservative estimates suggest that the average racial appraisal penalty is equal to roughly EUR 20,000. This figure is highly heterogeneous and can amount up to around EUR 58,000. Last, we provide evidence suggesting that this appraisal bias may very well pass through onto the final sales price and that it may be due to statistical discrimination.
Keywords: J15; R21; R31; 330; racial discrimination; housing; randomised online experiment